Online electricity theft detection and prevention scheme for smart cities. Issue 3 (17th September 2020) - Ballal, Makarand Sudhakar; Suryawanshi, Hiralal; Mishra, Mahesh Kumar; Jaiswal, Gajanan
Abstract : Electricity theft is a notable aspect of power distribution utilities due to advance in the non‐technical loss. It results imbalance between power supply and demand. It consequence overload of the distribution network and extraneous tariff invoke on legally connected consumers. The advance metering infrastructure is useful for an energy audit of every distribution transformer due to a communication facility. However, direct hooking on distribution overhead line or tapping from underground cables remains an interminable issue which has to be rigorously decimated. The objective of this study is to present real‐time electricity theft detection and prevention scheme (ETDPS) with the available infrastructure in the field. The proposed ETDPS is based on programmable logic control; it identifies the pilferage locations and estimates the power stolen by illegal consumers. The prototype is tested in the laboratory and the results demonstrate that the ETDPS works satisfactorily under diversified operating conditions. The proposed scheme is implemented as a part of their Smart City Pilot Project by Maharashtra State Electricity Distribution Company Limited, Nagpur (India) and the performance demonstrates its feasibility.